NIAT BELI PRODUK HIJAU DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI INDONESIA - Vilaningrum, Maria Angela Diva (Modus, 2024)
Green consumption has become the focus of consumers and companies. The Sustainable Development Goals (SDGs) raise many sustainability issues. Responsible consumption and production is one of the goals of the Sustainable Development Goals (SDGs). Consumption of environmentally friendly products can reduce the environmental and social impact caused by production and consumption. The purpose of this study is to determine the purchase intention of green products and the factors that influence it, namely attitude, subjective norms, perceived behavioral control, price awareness,  perceived consumer effectiveness, green product knowledge, and green product awareness.  This research is quantitative research with self-administered survey online. 174 respondents were taken using non-probability sampling with purposive sampling The first stage of data analysis is instrument testing, then multiple linear regression analysis. F-test and t-test for research model testing and hypothesis testing. The results showed that attitude affected the purchase intention of green products (H1 supported), subjective norms had no effect on the purchase intention of green products (H2 was not supported),  perceived behavioral control had an effect on the purchase intention of green products (H3 supported), price awareness affected the purchase intention of green products (H4 supported), perceived consumer effectiveness does not affect the purchase intention of green products (H5 is not supported), knowledge of green products affects the purchase intention of green products (H6 supported). Awareness of green products affects the purchase intention of green products (H7 supported). Keywords: purchase intention green product; Theory of Planned Behaviour; price consciousness; perceived consumer effectiveness. Konsumsi hijau telah menjadi fokus konsumen dan perusahaan. Sustainable Development Goals (SDGs) mengangkat banyak masalah keberlanjutan. Responsible consumption and production adalah salah satu tujuan Tujuan Pembangunan Berkelanjutan (SDGs). Konsumsi produk ramah lingkungan dapat mengurangi dampak lingkungan dan sosial yang disebabkan oleh produksi dan konsumsi. Tujuan penelitian ini adalah untuk mengetahui niat beli produk hijau dan factor-faktor yang mempengaruhinya yaitu attitude, norma subjetif, perceived behavioral control, kesadaran harga, perceived consumer effectiveness, pengetahuan produk hijau, kesadaran produk hijau. Penelitian ini merupakan penelitian kuantitatif dengan self-administered survey secara online. 174 responden diambil menggunakan non probability sampling dengan purposive sampling Tahap pertama pada analisis data adalah pengujian instrument, selanjutnya analisis regresi linear berganda. Uji F dan Uji t untuk pengujan model penelitian dan pengujian hipotesis. Hasilnya menunjukkan bahwa attitude  berpengaruh pada niat beli produk hijau (H1 terdukung), norma subjektif tidak berpengaruh pada niat beli produk hijau (H2 tidak terdukung), perceived behavioral control berpengaruh terhadap niat beli produk hijau (H3 terdukung), kesadaran harga berpengaruh terhadap niat beli produk hijau (H4 terdukung), perceived consumer effectiveness tidak berpengaruh terhadap niat beli produk hijau (H5 tidak terdukung), pengetahuan produk hijau berpengaruh terhadap niat beli produk hijau (H6 terdukung), dan kesadaran produk hijau berpengaruh terhadap niat beli produk hijau (H7 terdukung). Kata kunci: niat beli produk hijau; Theory of Planned Behaviour; kesadaran harga; perceived consumer effectiveness.